VDR gene FokI polymorphism as a poor prognostic factor for papillary thyroid cancer. Issue 11 (November 2018) - Beysel, Selvihan; Eyerci, Nilnur; Pinarli, Ferda Alparslan; Apaydin, Mahmut; Kizilgul, Muhammed; Caliskan, Mustafa; Ozcelik, Ozgur; Kan, Seyfullah; Cakal, Erman
This is the first study to investigate the effect of vitamin D receptor ( VDR ) gene single-nucleotide polymorphisms on the clinicopathologic features of papillary thyroid cancer in Turkey. A total of 165 patients with papillary thyroid cancer and 172 controls were included in this case–control study. VDR gene single-nucleotide polymorphisms FokI (rs2228570), BsmI (rs1544410), ApaI (rs7975232), and TaqI (rs731236) were evaluated using reverse-transcription polymerase chain reaction. VDR gene polymorphisms BsmI, ApaI, and TaqI did not differ between the papillary thyroid cancer group and control group (p > 0.05, each). BsmI, ApaI, and TaqI were not associated with papillary thyroid cancer risk. The VDR gene FokI CT/TT genotype was associated with an increased papillary thyroid cancer risk (CT vs CC: odds ratio = 1.71, 95% confidence interval = 1.15–2.76, p = 0.028; TT vs CC: odds ratio = 2.44, 95% confidence interval = 1.29–4.62, p = 0.005; CT/TT vs CC: odds ratio = 1.88, 95% confidence interval = 1.20–2.96, p = 0.006; CT/CC vs TT: odds ratio = 1.80, 95% confidence interval = 1.05–3.20, p = 0.041). VDR gene polymorphisms were not in linkage disequilibrium. The FokI TT genotype was associated with having T3 and T4, stage III/IV, extra-thyroidal invasion. The FokI CT/TT or TT genotype was associated with developing N1 status, multifocality, tumor size ≥10 mm, and treatment with radioiodine therapy. Persistence/recurrence did not differ between the FokI genotypes. Carriers of the FokI T allele were at an increased risk of more advanced tumor-node-metastasis stage, greater tumor size, multifocality, and extra-thyroidal invasion of papillary thyroid cancer compared with the CC genotype. VDR gene FokI T allele and TT genotype correlated with aggressiveness of papillary thyroid cancer; thus, FokI could be useful as a poor prognostic factor to assess the high risk of papillary thyroid cancer.